2010
DOI: 10.1111/j.1582-4934.2009.00792.x
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant methylation and associated transcriptional mobilization of Alu elements contributes to genomic instability in hypoxia

Abstract: Hypoxia is an integral part of tumorigenesis and contributes extensively to the neoplastic phenotype including drug resistance and genomic instability. It has also been reported that hypoxia results in global demethylation. Because a majority of the cytosine-phosphate-guanine (CpG) islands are found within the repeat elements of DNA, and are usually methylated under normoxic conditions, we suggested that retrotransposable Alu or short interspersed nuclear elements (SINEs) which show altered methylation and ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 42 publications
(56 reference statements)
2
25
1
1
Order By: Relevance
“…In particular, we found that the B1 SINE repeat showed high upregulation (see below) under severe hypoxia in the BMR brain. A similar mode of regulation was reported for human Alu SINEs that were shown to be transcriptionally upregulated under hypoxic conditions, presumably contributing to genomic instability in tumours 48 .…”
Section: Resultssupporting
confidence: 67%
“…In particular, we found that the B1 SINE repeat showed high upregulation (see below) under severe hypoxia in the BMR brain. A similar mode of regulation was reported for human Alu SINEs that were shown to be transcriptionally upregulated under hypoxic conditions, presumably contributing to genomic instability in tumours 48 .…”
Section: Resultssupporting
confidence: 67%
“…[42][43][44] In other words, hypoxia is highly related to hypomethylation and may necessarily be active in maintaining low levels of DNA modifications required for stemness or tumorigenesis.…”
Section: Resultsmentioning
confidence: 99%
“…ROS (reactive oxygen species) generated by infiltrating leukocytes (macrophages and neutrophils) and resulting from intermittent hypoxia induced by tissue damage, might also lead to increased mutation rates and alter the epigenetic profiles of epithelial and stromal cells. Indeed, a recent report described alterations in DNA methylation in hypoxic conditions (Pal et al 2009).…”
Section: K Polyak and R Kallurimentioning
confidence: 99%